2004
DOI: 10.1159/000081855
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Retinopathy and Cognitive Impairment among Hypertensive Subjects

Abstract: Background: The relationship between hypertension and cognitive impairment has been investigated in the literature; several clinical studies suggested a relationship between hypertension and retinopathy. Methods: We examined the relationship between the retinopathy status and cognitive functions by using the Mini-Mental State Examination (MMSE) among hypertensive subjects older than 40 years who were admitted to our Family Medicine, Internal Medicine and Ophthalmology clinics. The subjects were categorized int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In this population of older persons, an association was found between retinal microvascular signs (retinopathy and venular dilation) and cognitive impairment, particularly in persons with hypertension. The findings are consistent with reports from three other studies, which indicated an association between retinopathy signs and various measures of cognitive impairment such as the MMSE, Digit Symbol Substitution Test, and Delayed Word Recall Test, as well as with clinical dementia, with associations strongest in persons with hypertension 6,7,24 . A case‐control study reported a similar relationship between retinopathy and cognitive impairment in persons with hypertension 6 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this population of older persons, an association was found between retinal microvascular signs (retinopathy and venular dilation) and cognitive impairment, particularly in persons with hypertension. The findings are consistent with reports from three other studies, which indicated an association between retinopathy signs and various measures of cognitive impairment such as the MMSE, Digit Symbol Substitution Test, and Delayed Word Recall Test, as well as with clinical dementia, with associations strongest in persons with hypertension 6,7,24 . A case‐control study reported a similar relationship between retinopathy and cognitive impairment in persons with hypertension 6 .…”
Section: Discussionsupporting
confidence: 91%
“…Cerebral vascular disease is hypothesized to be involved in the pathogenesis of cognitive impairment, 1,2 with considerable data supporting the role of macrovascular disease 1,3,4 . In contrast, the role of subcortical microvascular disease in cognitive impairment is less clear, although studies indicate a substantial contribution, particularly in older persons 5 and those with cardiovascular risk factors such as hypertension 2,6,7 . Clinical data on the involvement of microvascular disease in cognitive impairment are sparse, principally because of the difficulty in noninvasively imaging the cerebral microcirculation 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the eight studies meeting our inclusion criteria,16 – 23 two were subsequently excluded, as they did not fulfil the quality criteria 16 17. The key details of the six included studies are summarised in tables 1, 2.…”
Section: Resultsmentioning
confidence: 99%
“…6 This relationship between retinal microvascular abnormalities and cognitive impairment is especially significant for populations at high risk for cognitive impairment. 7-9 For example, among participants with type I or type II diabetes, retinopathy has been reported to be associated with cognitive impairment, 8, 10 and among participants with hypertension, it has been shown that those with retinopathy may be two times more likely to have dementia or cognitive impairment. 2, 4 …”
mentioning
confidence: 99%